Antimicrobial activities, DNA interactions, spectroscopic (FT-IR and UV-Vis) characterizations, and DFT calculations for pyridine-2-carboxylic acid and its derivates - (:unkn) unknown (ELSEVIER, 2018)
In this paper, pyridine-2-carboxylic acid, also known as picolinic acid (pic), and its two derivate, 4-methoxy-pyridine-2-carboxylic acid (4-Mpic) and 4-chloro-pyridine-2-carboxylic acid (4-Clpic) have been characterized by FT-IR and UV-Vis spectroscopy techniques as well as DFT calculations. B3LYP level of Density Functional Theory (DFT) method was used to obtain ground state geometries, vibration wavenumbers, first order hyperpolarizabilities and molecular electrostatic potential (MEP) surfaces for pic, 4Clpic and 4Mpic. The electronic absorption wavelengths and HOMO-LUMO energies were investigated by time dependent B3LYP (TD-B3LYP) level with the conductor-like polarizable continuum model (CPCM). The effects of Cl atom and OCH3 group on HOMO-LUMO energy gaps and first order hyper-polarizability parameters of pic, 4Clpic and 4Mpic molecules were examined. All molecules were screened for their antibacterial activities against Gram-positive and Gram-negative bacteria and for their antifungal activities against yeast strains by using minimal inhibitory concentration method (MIC). All compounds (pic, 4Mpic and 4Clpic) have been found to be very active against to the Gram (+) and Gram (-) bacteria. The DNA interactions of pic, 4CIpic and 4Mpic were analyzed by molecular docking simulations, and the interaction of the 4Mpic molecule with DNA is found to be higher than 4Clpic and pic. (c) 2017 Elsevier B.V. All rights reserved.
Keywords: Picolinic acid; Antibacterial activity; DNA binding; FT-IR; UV-Vis; DFT; NONLINEAR-OPTICAL PROPERTIES; X-RAY-STRUCTURE; CRYSTAL-STRUCTURE; BROMOBENZENE DERIVATIVES; MOLECULAR-STRUCTURE; II COMPLEX; PICOLINATE; SPECTRA; CHLOROBENZENE; ENERGIES